2021
DOI: 10.3390/atmos12030309
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Element Mass Concentrations in Ambient Aerosols by Combination of Cascade Impactor Sampling and Mobile Total Reflection X-ray Fluorescence Spectroscopy

Abstract: Quantitative chemical analysis of airborne particulate matter (PM) is vital for the understanding of health effects in indoor and outdoor environments, as well as for enforcing EU air quality regulations. Typically, airborne particles are sampled over long time periods on filters, followed by lab-based analysis, e.g., with inductively coupled plasma mass spectrometry (ICP-MS). During the EURAMET EMPIR AEROMET project, cascade impactor aerosol sampling is combined for the first time with on-site total reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(38 reference statements)
1
9
0
1
Order By: Relevance
“…Cut-off diameters below 1 µm were verified through a comparison measurement using an aerosol spectrometer 36 . Total particle mass agreed well with reference filter sampling and size distributions were found to be similar to those obtained using a commercial Dekati impactor 37 . The sampling time was 8 h in both cases, during daytime including the main time for medical interventions.…”
supporting
confidence: 72%
“…Cut-off diameters below 1 µm were verified through a comparison measurement using an aerosol spectrometer 36 . Total particle mass agreed well with reference filter sampling and size distributions were found to be similar to those obtained using a commercial Dekati impactor 37 . The sampling time was 8 h in both cases, during daytime including the main time for medical interventions.…”
supporting
confidence: 72%
“…Engineered nanoparticles, often having small size distributions, are ideal nanoobjects to be characterized by GIXRF [27] with respect to surface coverage and particle composition. With respect to characterizations of nanoparticles and environmental aerosols, both TXRF [25] and GIXRF [26] have shown their analytical capabilities to quantify elemental mass depositions of size-fractionated nano-and microparticles collected by means of cascade impactors on flat substrates. A reference-free GIXRF quantification mode [26] allows one to determine the angular ranges of validity for the correct quantification of specific elemental mass depositions.…”
Section: Figurementioning
confidence: 99%
“…Besides revealing information about elemental mass depositions and related chemical binding states of nanomaterials by means of XRF and XAFS, complementary chemical information can be revealed using high-resolution X-ray emission spectrometry (XES), which often provides a different discrimination capability depending on the specific With respect to characterizations of nanoparticles and environmental aerosols, both TXRF [25] and GIXRF [26] have shown their analytical capabilities to quantify elemental mass depositions of size-fractionated nano-and microparticles collected by means of cascade impactors on flat substrates. A reference-free GIXRF quantification mode [26] allows one to determine the angular ranges of validity for the correct quantification of specific elemental mass depositions.…”
Section: High-resolution X-ray Spectrometrymentioning
confidence: 99%
“…In this sense, Prost et al (2017) demonstrated that the direct collection of aerosol particles on greased quartz reflectors using a PM10 impactor, reduce the risk of contamination and samples can be measured directly and undiluted. In a recent publication, acrylic glass discs and silicon waters were shown to be suitable carriers, with sufficiently smooth and clean surfaces, for TXRF analysis of PM as well (Seeger et al, 2021). Finally, in addition to PM characterization, TXRF has also been used to determine the concentration of airborne Hg (Böttger et al, 2020).…”
Section: Atmospheric Particulate Mattermentioning
confidence: 99%